On some properties of k-circulant matrices with the generalized Pell-Padovan numbers - Soykan, Yüksel; Taşdemir, Erkan (Journal of Innovative Applied Mathematics and Computational Sciences, 2026)
In this paper, we investigate the properties of the k-circulant matrix generated by the generalized Pell–Padovan numbers. We derive explicit formulas for the sum of entries, the maximum column sum norm (· _1), the maximum row sum norm (· _∞ ), the Frobenius (Euclidean) norm (· _F), as well as the eigenvalues and determinant of this matrix. Furthermore, we establish upper and lower bounds for its spectral norm (· _2), thereby providing a comprehensive analysis of the structural andspectral characteristics of the k-circulant matrix associated with thegeneralized Pell–Padovan sequence.